Study of relationships between correlation-immunity and balanceness based on Boolean functions - LI Wei-wei (Tongxin xuebao)
E-derivative and derivative were introduced to deeply study internal structure of Boolean function,and analyzed the cryptographic properties of Boolean function,which was a new subject in cryptology.The relationships between correlation-immunity and balanceness was analyzed,and obtain some important results which could not be obtained by analyzing the exterior structure of Boolean function at all.Beyond that,for researching on the correlation immunity of balanced H-Boolean function which play a important role in cryptology,here also give a new research methods to improve the anti-attack ability of cryptosystem.